Capricci luterani? Michelangelo artista e poeta nel contesto del dibattito religioso del Cinquecento / Michelangelo, Artist and Writer, and the Religious Debates of the Sixteenth Century - Ott, Christine; Aurenhammer, Hans; Föcking, Marc; Nova, Alessandro (De Gruyter, 2023)
Does Michelangelo's art reflect Catholic orthodoxy or is it the work of a follower of the Reformation, forced to act in secret? The question of Michelangelo's religious beliefs is still debated, and the positions taken tend to remain unilateral. This volume gathers contributions by art historians, literary scholars, and historians of religion who address this question in all its complexity.